Hospital‐acquired anemia: Prevalence, outcomes, and healthcare implications. Issue 9 (19th July 2013) - Koch, Colleen G.; Li, Liang; Sun, Zhiyuan; Hixson, Eric D.; Tang, Anne; Phillips, Shannon C.; Blackstone, Eugene H.; Henderson, J. Michael
Abstract : BACKGROUND: Evidence suggests that patients with normal hemoglobin (Hgb) levels on hospital admission who subsequently develop hospital‐acquired anemia (HAA) may be at risk for adverse outcomes. Our objectives were to (1) determine the prevalence of HAA and (2) examine whether HAA is associated with increased mortality, length of stay (LOS), and total hospital charges. METHODS: The population consisted of 417, 301 adult hospitalizations from January 1, 2009 to August 31, 2011, in an academic medical center and 9 community hospitals. Patients with anemia on admission, and hospitals in the health system without available laboratory data were excluded; 188, 447 hospitalizations were included in the analysis. Demographics, comorbidities, and outcomes were retrieved from administrative data; Hgb values were taken from the electronic medical record. Regression modeling was used to examine the association between demographics, comorbidity, hospitalization type, and HAA variables (mild: Hgb >11 and <12 g/dL for women, and >11 and <13 g/dL for men; moderate: Hgb 9.1 to ≤11.0 g/dL; severe: Hgb ≤9.0 g/dL) on mortality, LOS, and hospital charges. RESULTS: Among 188, 447 hospitalizations, 139, 807 patients (74%) developed HAA: mild, 40, 828 (29%); moderate, 57, 184 (41%); and severe, 41, 795 (30%). Risk‐adjusted odds ratios and 95% confidence intervals for in‐hospital mortality with HAA were: mild, 1.0 (0.88–1.17; P = 0.8); moderate, 1.51 (1.33–1.71, P < 0.001); and severe, 3.28 (2.90–3.72, P < 0.001). Risk–adjusted relative mean LOS and hospital charges relative to no HAA were higher with HAA: LOS: mild, 1.08 (1.08–1.10, P < 0.001); moderate, 1.28 (1.26–1.29, P < 0.001); severe, 1.88 (1.86–1.89, P < 0.001). Hospital charges: mild, 1.06 (1.06–1.07, P < 0.001); moderate, 1.18 (1.17–1.19, P < 0.001); severe, 1.80 (1.79–1.82, P < 0.001). CONCLUSIONS: HAA is common and associated with increased mortality and resource utilization. Factors related to its development necessitate further study. Journal of Hospital Medicine 2013;8:506–512. © 2013 Society of Hospital Medicine